INTEGRASI PENDEKATAN EKOPEDAGOGI DALAM MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI EKOSISTEM SISWA KELAS V SDN 4 TANGGEL - PRATAMA, YOGA; PURNAWANTO, AHMAD TEGUH; ROFIQ, MUHAMMAD AUNUR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to intensify fifth-grade student’s natural and social sciences learning outcomes on ecosystem material through the integration of ecopedagogy into the Student Teams Achievement Division (STAD) cooperative learning model. The study was conducted at Public Elementary School 4 Tanggel involving 16 fifth-grade student’s. The research followed two phases consist of planning, action, observation, and reflection. Data were collected using learning achievement tests, student activity observation sheets, field notes, and documentation. The action integrated STAD stages with ecopedagogical activities, including contextual ecosystem problems, group discussion, ecological reflection, and presentation of environmentally responsible solutions. Data were analyzed descriptively by comparing the mean score, the number of students achieving mastery, and classical mastery across phases. The findings showed that the mean score increased from 78.28 in Phase I to 80.00 in Phase II. The number of passed students increased from 14 of 16 students (87.50%) to 15 of 16 students (93.75%). Classroom observations also indicated improvement in participation, cooperation, confidence, and student’s ability to connect ecosystem concepts with environmental care. The study concludes that ecopedagogy-integrated STAD can strengthen meaningful IPAS learning by combining concept mastery, collaborative learning, and ecological awareness.